THE EFFECT OF WORK MOTIVATION AND REWARDS ON EMPLOYEES' WORK PRODUCTIVITY IN THE PRODUCTION DEPARTMENT AT PT. MAYORA INDAH TBK IN TANGERANG REGENCY - Ramadhan, Muhammad Dzikri Syahrul; Khaeruman, Khaeruman; Abduh, Edi Muhammad (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
This study aims (1) To ascertain whether work motivation significantly influences employee productivity within the Production Department at PT. Mayora Indah Tbk in Tangerang Regency.  (2) To determine whether rewards have a significant partial effect on employee work productivity in the Production Department at PT. Mayora Indah Tbk in Tangerang Regency. (3) To determine whether work motivation and rewards significantly affect employee work productivity in the Production Department at PT. Mayora Indah Tbk in Tangerang Regency. This study uses a quantitative approach with an associative method, where data is collected through a questionnaire and analyzed using SPSS version 26. A questionnaire trial was conducted to ascertain the validity and reliability of the questionnaire after it was distributed to the research sample as part of the data collection technique that employs a Likert scale. Regression and correlation analyses were implemented to evaluate the findings of the investigation. The results of this study suggest the level of employee productivity at PT. Mayora Indah Tbk is significantly influenced by work motivation and rewards. The significance test shows that work motivation (X1) has a t-count value of 5.556 with a contribution of 96.5% to employee productivity (Y). Reward (X2) has a t-value of 9.416 with a contribution of 85.4%. Simultaneously, work motivation and reward contribute 90.7% to employee productivity, with a calculated f value of 73.914